ChemInform Abstract: DFT Calculations of Electronic and Transport Properties of Substituted Mn4Si7. Issue 3 (21st January 2014) - Allam, A.; Boulet, P.; Record, M.‐C.
Abstract Electronic and transport properties of substituted Mn4Si7 are evaluated by DFT calculations with Co, Mo, Ru, Rh, Cd, Ir, and Sb, Te, Pb, Bi as substituents for Mn and Si, resp.